Dissolution and pharmacokinetics profile of acetylsalicylic acid in rabbit plasma following oral ingestion of acetylsalicylic acid microcapsules - Faizatun; Ni Made Dwi Sandhiutami (Faculty of Pharmacy, Universitas Pancasila, 2026)
Acetylsalicylic acid (80 mg) suppresses thromboxane A2 (TXA-2) formation, thereby reducing platelet aggregation and is used as an antiplatelet agent. Oral administration of acetylsalicylic acid causes gastrointestinal bleeding; therefore, acetylsalicylic acid microcapsules have been developed, which are less soluble in stomach acid but dissolve in intestinal fluid. This study aimed to evaluate the concentration, dissolution, and bioavailability of acetylsalicylic acid (ASA) microcapsules. Microcapsules were prepared using the microencapsulation method with an alginate crosslinking technique, with calcium chloride as the crosslinker. The concentration of acetylsalicylic acid and the dissolution of microcapsules were determined in vitro. The bioavailability of 80 mg acetylsalicylic acid microcapsules was studied in rabbits that were orally administered of 80 mg. Blood sampling was carried out at 0, 0.5, 1, 2, 4, 6, 8, 8.5, 9, 9.5, 10, 12, 14, 16, 24, and 30 h. In this study, the percentage of acetylsalicylic acid in the microcapsules was 24.08±0.59%. The dissolution test at the acid stage showed that acetylsalicylic acid was still released at 40.09% in 90 min. In the bioavailability test, a lag time of absorption of less than 1 h was obtained, peak plasma levels of 2.06 μg/mL were achieved within 9.16 h after microcapsule administration, and the area under the curve was 15.98 μg · h/mL. It can be concluded that the release of acetylsalicylic acid from microcapsules in the acidic medium indicates incomplete entrapment, and there is a lag time, indicating inhibition of drug release due to the microencapsulation process.